Relationship between falls, knee osteoarthritis, and health-related quality of life: data from the Osteoarthritis Initiative study - Vennu V (Dove Medical Press, 2014)
Vishal Vennu, Saad M BindawasDepartment of Rehabilitation Science, College of Applied Medical Sciences, King Saud University, Riyadh, Saudi ArabiaBackground: The purpose of this study was to examine the relationship between self-reported falls, doctor-diagnosed knee osteoarthritis (OA), and health-related quality of life (HRQoL). We hypothesized that falls and knee OA would be associated with poor HRQoL on both disease-specific and generic measures.Methods: This cross-sectional study used data from the publicly available Osteoarthritis Initiative data sets. A total of 4,484 subjects aged 45–79 years at baseline were divided into three subpopulations: those who had neither a history of falling nor doctor-diagnosed knee OA; those who had either a self-reported history of falling or doctor-diagnosed knee OA; and those who had both a self-reported history of falling and doctor-diagnosed knee OA. HRQoL was assessed using both disease-specific and generic measures. Multiple regression analyses were used to examine the relationship between self-reported falls, doctor-diagnosed knee OA, and HRQoL assessed using the Knee Injury and Osteoarthritis Outcome Score-Quality of Life (KOOS-QoL) subscale and two Short Form-12 (SF-12) summary scales. The models were adjusted for participant sociodemographic, lifestyle, and clinical characteristics.Results: Falls and knee OA were significantly associated with lower scores on the KOOS-QoL (β= −34.4, standard error 2.27, P≤0.0001) and on the physical component scale of the SF-12 (β= −9.44, standard error 0.90, P<0.0001). No significant relationship was found with the mental component scale score when adjusted for sociodemographic, lifestyle, and clinical characteristics.Conclusion: When compared with those having neither a self-reported history of falling nor doctor-diagnosed knee OA and those with a self-reported history of falling or doctor-diagnosed knee OA, persons with both conditions (falls and knee OA) had significantly lower KOOS-QoL and physical component scale scores after adjusting for sociodemographic, lifestyle, and clinical characteristics. Future research should assess potential mediating factors in an effort to improve HRQoL in persons with knee OA who are at high risk of falling.Keywords: osteoarthritis, quality of life, falls